From Industry to Academia: A Leading Orthopaedic CEO’s Journey into Research - DaCosta, Albert (Journal of the Foot & Ankle, 2025)
As a child, I never dreamt of feet. I never considered their importance or complexity. I certainly never said, “One day I will grow up and improve people’s ability to walk.” And yet, I find myself in a place where I am inspired every day to seek answers, think creatively, and improve lives. Today, I can say with confidence and childlike wonder: my purpose is feet. I grew up in a Portuguese household with three amazing siblings, the youngest of whom was born with spina bifida. Our family was close-knit, and I spent much of my childhood by my sister’s side. Through her, I experienced life with a disability—the longing to blend in, the silent resilience of wanting to feel “normal.” I remember taking her trick-ortreating in a basket on a three-wheeled bike so she could share in the joy of childhood. I dreamt, even then, of finding a cure. I never imagined I would spend my career trying to create solutions that might fulfill that dream not just for her, but for countless others. I didn’t become a doctor—a minor disappointment to my loving Portuguese mother—but I did become an engineer. And I fell in love with the world of orthopedics through sales. I explored hips, knees, spine, and sports medicine, but it was foot and ankle that captured my heart. The field was young, diverse, and underdeveloped—with over 100 indications and very limited data. I remember being asked for 10-year follow-up data and thinking, “We are lucky to have any data at all.” The foot itself is a miracle of biomechanics. From the plantar fascia controlling arches and force vectors to the interplay between rigid and flexible columns—we understand so little about something so fundamental. Every day, I learn more, and every day I am more convinced that I have found the purpose I never knew I needed. This is bigger than any financial goal. I know I can help. I vividly recall a conversation with Dr. Michael Houghton about syndesmotic reduction. He described how subtle and tactile the procedure is—how you rely on a 1 mm overlap and “feel” the tilt of the talus. Years later, finite element modeling at the University of Virginia quantified what he described: a deviation of less than 1 mm alters pressure in the talar gutter enough to initiate arthritis. It confirmed what I already believed—this field needs precision, clarity, and innovation. In 2010, I co-founded Paragon 28 with Lee Rosenthal in his basement in Birmingham, Alabama. We didn’t fully grasp the scale of what we were building. Understandably, our wives were not thrilled when we announced we were quitting our jobs and investing our life savings in a dream. At the time, Foot & Ankle was growing at 9–10% annually—an anomaly in orthopaedics—and larger companies took notice. But to many of them, it was just a growth opportunity. That offended me. I walked trade show floors seeing the same recycled ideas. Changing anodization color or screw diameter by 1 mm and calling it innovation? That is not what transforms patient care. We believed our market deserved better—and that conviction built one of the most effective Foot & Ankle companies in the industry. A company built on research first, without a product in mind. Research that would drive the next generation of understanding. We cared deeply about leaving a legacy of transforming an entire segment. By 2019, we crossed $100 million in revenue—a milestone that required us to evolve. What got us there would not get us to the next $100 million. We conducted a surgeon survey that made one thing clear: innovation was not yet changing lives. We asked ourselves hard questions. Would outcomes with our “cool” solutions actually outperform k-wires? That was the moment we committed to enabling technologies.